Participatory integrated watershed management: Evolution of concepts and methods in an ecoregional program of the eastern African highlands - German, L.; Mansoor, H.; Alemu, G.; Mazengia, W.; Amede, Tilahun; Stroud, Ann (2007)
This paper focuses on the conceptual evolution of watershed management within the context of an action research program operating in the highlands of eastern Africa, as informed by both theory and practice. Following a review of the watershed management literature, and brief program and methodological overviews, the paper explores in detail the concepts of ''participation'' and ''integration'' in watershed management. Conceptual and methodological dimensions of the terms are discussed in the context of a watershed implementation process, clarifying how ''watershed issues'' are defined by local users, how ''stakeholders'' are defined with respect to those issues, and how participation and integration may be operationalized in practice. Data are selectively chosen from different pilot sites to illustrate how concepts underlying watershed management have been refined, and methods improved. It is clear that ''participation'' n problem diagnosis and program implementation must move beyond community-level fora to socially- disaggregated processes and explicit management of trade-offs to diverse groups. Secondly, integration does not come about through implementation of parallel interventions, but rather through an explicit analysis of potential trade-offs and synergies of interventions to diverse system components, and strategies to define and reach systems-level goals. Each approach requires attention to ways to optimize returns to diverse social groups and system components while minimizing negative spin-offs. The paper concludes with a discussion of implications for agricultural research and development in the eastern African region.